The Effect of Solid-State Anaerobic Disgestion (Ss-Ad) and Liquid Anaerobic Disgestion (L-Ad) Method in Biogas Production of Rice Husk - Budiyono, Budiyono; Sumardiono, Siswo; Fofana, Fadillah Fathir Mahmud; Fauzi, Ihwan; Hadiyarto, Agus (Vocational College of Universitas Diponegoro, 2019)
Rice husk is one of the agricultural waste from rice crop residue which has high potential to be processed into biogas. The purpose of this research is to study the effect of solid state anaerobic digestion and liquid anaerobic digestion on biogas production from rice husk waste. The anaerobic digestion laboratory scale used in this experiment is operated in a batch system and at room temperature. This method is added with chemical and biological pretreatment that was NaOH and microbial consortium. Total solid (TS) was varied from 5%, 7%, 9%, 11% which is L-AD and 17%, 19%, 21%, 23% are SS-AD. Biogas results were measured using the water displacement method every two days to determine daily production. The results showed that with the addition of NaOH the total volume of biogas obtained by L-AD method (TS 9%) and SS-AD (TS 23%) were 1254 ml and 1397 ml. Production of biogas per unit of TS for L-AD method is 46,44 ml / grTS and for SS-AD is 20,246 ml / grts, while biogas production per reactor volume unit for L-AD method is 6,26 ml / ml reactor and for SS-AD method is 4.64 ml / ml reactor. The kinetics constant of biogas production with L-AD method obtained A, U, and λ respectively were 50,53 ml / grTS, 1.23ml / grTS.day, 11,71 day, while for SS-AD method obtained A, U , and λ respectively 21.07 ml / grTS, 0.6 ml / grTS.day, 6.2 days.